Ethnomatematics of geometry shape in the Gedongsongo Temple - Uswatun Khasanah; Yanuar Hery Murtianto; Kartinah Kartinah (Universitas negeri Yogyakarta, 2022)
The objective of the study is to explore and find out the ethnomathematics of Gedongsongo Temple, located in Central Java, Indoensia. The type of study is qualitative with an exploration way and ethnographic approach. The data obtained in the form of qualitative data, the source of research data obtained through observation, interviews, documentation, and study of literature related to Gedongsongo Temple. The data collection technique was done by questioning, observing, interviewing, and documenting. The results showed that the ethnomathematics of Gedongsongo Temple has the potential to be integrated into mathematics learning. Ethnomathematics that can be integrated includes the concept of flat area, volume of space, comparison/ratio, reflection, and symmetry. The flat-geometry concept is found in the several parts of Gedongsongo Temple including square, rectangle, triangle, and trapezoid. The spatial-geometry concept is also found in several parts of Gedongsongo Temple including cubes, blocks, tubes, and a triangle prism. Meanwhile, the comparison/ratio concept found is the Golden Ratio on the fore-temple of Perwara in the area of Candi Gedong III. The symmetry and reflection concept is found in Candi Gedong I. These concepts can be applied in mathematics learning as a contextual geometry problem as well as a way of introducing cultural elements to students.